SHADOW GLOBALIZATION - L. M. Kapitsa (Vestnik MGIMO-Universiteta)
The article reviews some development trends brought about by globalization, particularly, a growing tax evasion and tax avoidance, an expansion of illicit financial flows and the proliferation of a global criminal network. The author draws attention to some new phenomena, particularly, cosmopolitanization of some parts of national elites and a deepening divide between national interests and the private interests of elites as a consequence of financial globalization. Modern mass media, both Russian and foreign, tend to interpret globalization processes exclusively from the position of conformism, and for some of the researchers globalization became the "sacred cow", which one may only worship. Critical analysis of the processes associated with globalization is given a hostile reception. In response to criticism of globalization, one can hear the very same argument: "globalization in inevitable!" Such a state of affairs, the very least, causes perplexity. Some of the world development trends been observed over the past years raise serious concerns about the security and welfare of the peoples of the world. One of such trends has been the globalization of shadow economic activities. Methods of fight against the criminal economy been applied in international practice can be grouped into: 1) punitive enforcement (or criminal-legal) methods) and 2) socio-economic methods. As the results of various research works evidence punitive enforcement methods not supported by socio-economic measures not effective enough. Toughening the control over criminal economic activities in the absence of preventive and corrective actions aiming to neutralize institutional, social and other stimuli facilitating criminalization of economic activities can result in large losses of financial assets in the form of mass capital flight